Comparison of physicochemical characteristics and sensory attributes of four different chicken breeds from the genuine and selected local market - Selamat, Jinap; M. Zaidy, Nur A. N.; Zakaria, Nur S.; Juhari, Nurul H.; Murugesu, Suganya (Hindawi, 2022)
Village chicken is known as a high-quality product perception and sold at high prices. However, the authenticity of village chicken is doubted because colored chicken has been claimed as village chicken to fraud the consumers and to gain high profit. No stringent strategy has been implemented by the local authority on the authenticity of the claimed village chickens. Thus, the study aimed to determine the meat quality of different chicken breeds including village chicken, broiler chicken (Cobb), colored chicken (Hubbard), and layer chicken from genuine suppliers and chickens sold at different local markets based on the physicochemical characterization, textural properties, and sensory evaluation. Chicken breeds were obtained from genuine suppliers and slaughtered at the slaughtering house Universiti Putra Malaysia. Proximate composition, color, and textural properties were evaluated. Minitab-19 and SIMCA-13 software were used to analyze the results, applying analysis of variance and partial least squares discriminant analysis, respectively. The study revealed that some of the market-supplied chickens were not authentic based on the features studied. About 20% of market village chickens had possessed similar results as the control village chicken. It can be shown that 80% of the claimed village chicken sold in the market was not authentic village chicken. This study showed the differentiation in texture composition such as chewiness, hardness, gumminess, cohesiveness, resilience, and springiness, followed by protein content, ash content, and a and b values as an indicator to differentiate the authenticity of different chicken breeds.